2015
DOI: 10.1002/ajoc.201500295
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Pursuit of Diterpenoid Alkaloids: A Synthetic View

Abstract: The incorporation of nitrogen atoms into policyclic diterpenes has led to one of the most fascinatingg roup of natural products with cage-like structures:d iterpenoid alkaloids. Their singular architectural features and significant bioactivitiesm ade them highly pursued targets amongst the synthetic community over decades. At otal of seven types of diterpenoid alkaloid molecules have been synthesized thus far,a nd the research in this area experiencedanew climax in the past five years. With ab rief overview an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 70 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…1 Among the many structural classifications that have been established, the hetisine-type C 20 -diterpenoid alkaloids have emerged as compounds of particular interest. They possess one of the most complex frameworks of any of the diterpenoid alkaloids, with a tertiary amine embedded in a caged heptacyclic core (see nominine (1), Figure 1), and are one of the most prominent diterpenoid alkaloid types, with over 120 known members.…”
mentioning
confidence: 99%
“…1 Among the many structural classifications that have been established, the hetisine-type C 20 -diterpenoid alkaloids have emerged as compounds of particular interest. They possess one of the most complex frameworks of any of the diterpenoid alkaloids, with a tertiary amine embedded in a caged heptacyclic core (see nominine (1), Figure 1), and are one of the most prominent diterpenoid alkaloid types, with over 120 known members.…”
mentioning
confidence: 99%
“…These synthetic campaigns culminated in the completion of formal and total syntheses of a subset of C 20 diterpenoid alkaloids, namely nominine ( 1 ), atisine ( 4 ), isoatisine ( 5 ), isoazitine ( 6 ), dihydroajaconine, gymnandine, spiramines C and D, and cochlearenine . However, most of these synthetic routes require a large number of steps and are restricted to a very particular structure . Two notably short and elegant routes include Gin's total synthesis of nomine (16 steps), and Baran's semisynthesis of isoatisine (13 steps from (−)‐steviol) .…”
Section: Figurementioning
confidence: 99%
“…1315 These nitrogen-containing diterpenoids have attracted significant attention from the synthetic community as a result of their diverse biological activity and structural complexity. 16 The earliest synthetic efforts focused on the C 20 alkaloids, resulting in syntheses of atisine ( 1 ), 17,18 garryine, 19,20 veatchine, 20,21 napelline, 22 and nominine ( 2 ). 23 Baran et al demonstrated a unified approach to (−)-methyl atisenoate, its alkaloidal counterpart (−)-isoatisine ( 3 ), and the hetidine skeleton.…”
mentioning
confidence: 99%